Immune Response After Measles Vaccination - Bhardwaj A.K; Gupta B.P; Bhardwaj P.K; Swami H.M; Sood D.K; Ahluwalia S.K; Vaidya N.k (Wolters Kluwer Medknow Publications, 1991)
Measles immunization of 192 under 5 years of age children was undertaken and the overall seroconversion was 76.0%. Seroconversion rate in the age group of 9-12 months was 70.9% and it was 100% after one year. Immune response in malnourished children was more as compared to normal children. There were negligible side reactions after measles vaccination, and this vaccine passed normal potency tests under field conditions.